Coffee and Covid - Mansor, Nur Aliah; Din, Norrina (Universiti Teknologi MARA, Terengganu, 2022)
Coffee, like life, has bitter and sweet aspects that do not change with time, much as the bittersweet narrative of the Keluarga Malaysia’s life told in Covid-19. After crude oil, coffee is the world’s second most valuable commodity [1]. Malaysians drink 2.5 cups of coffee every day on average [2]. Malaysians frequent coffee shops and kopitiam as places to meet friends. Before the advent of social media, here is where they would “status update” to their friends.